2016
DOI: 10.1111/trf.13607
|View full text |Cite
|
Sign up to set email alerts
|

Difficult to swallow: warm autoimmune hemolytic anemia in a Jehovah's Witness treated with hemoglobin concentrate complicated by achalasia

Abstract: Early recognition of the need and ready familiarity with its properties on the part of the physician are critical to the utilization of HBOC-201 in a safe and timely fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The 27 units used in the third case equal the largest volume a patient has received to date and survived (Z. Zafirelis, CEO of HbO2 Therapeutics, personal communication, June 9, 2017). This is equal to the dose cited in a case by Epperla and coworkers …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 27 units used in the third case equal the largest volume a patient has received to date and survived (Z. Zafirelis, CEO of HbO2 Therapeutics, personal communication, June 9, 2017). This is equal to the dose cited in a case by Epperla and coworkers …”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated a 59% blood transfusion avoidance and no statistical difference in mortality between the HBOC‐201 and RBC transfusion arms of the study. However, the number of serious adverse events was higher in the HBOC‐201 arm (25% vs. 17%) including an increased risk of myocardial injury, stroke, and achalasia . Due to the lack of mortality benefit and increased risk of adverse events, the FDA has only approved HBOC‐201 for expanded access at this time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it contains no cell membrane, it is compatible with all blood types (no cross matching is needed The side effect profile of the second generation HBOC's is much preferable to that of the first (4). Reported class effects of HBOC use include hypertension, esophageal dysmotility and increased risk for myocardial infarction, all of which are related to vasoconstriction secondary to increased nitric oxide scavenging in these products (5). HBOC-201 in particular, has not been reported to increase risk of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Jehovah's Witnesses in general will not receive "primary" blood components which include red blood cells, platelets and plasma. Other components, including albumin, clotting factors and HBOCs are considered "conscience items" through the church, where-in the individual can decide for themselves if they wish to receive them (5). With an estimated 1.2 million Jehovah's Witnesses in the United States alone, alternative treatment options for this patient population are imperative (5).…”
Section: Discussionmentioning
confidence: 99%